Comparison of the accuracy of diagnoses of oral potentially malignant disorders with dysplasia by a general dental clinician and a specialist using the Taiwanese Nationwide Oral Mucosal Screening Program. - Tien-En Chiang; Yu-Chun Lin; Chi-Tsung Wu; Cheng-Yu Yang; Sheng-Tang Wu; Yuan-Wu Chen (PLoS ONE)
Screening for oral potentially malignant disorders (OPMDs) with dysplasia in high-risk groups is suggested in countries with a high prevalence of the disorders. This study aimed to compare the accuracy of diagnoses of OPMDs with dysplasia made by a primary examiner (general dental clinician) and a specialist (oral and maxillofacial surgeon) using the current Taiwanese Nationwide Oral Mucosal Screening Program (TNOMSP). A total of 134 high-risk participants were enrolled for oral mucosal screening via the TNOMSP. A primary examiner and a specialist examined each participant. Mucosal biopsies were obtained and subjected to histopathological analysis. The OPMD most frequently diagnosed by the primary examiner was thin homogeneous leukoplakia (48/134; 35.8%), and in 39/134 participants (29.1%) the diagnosis was uncertain, but abnormalities were suggested. The OPMDs most frequently diagnosed by the specialist were erythroleukoplakia (23/134; 17.2%) and thin homogeneous leukoplakia (21/134; 15.7%), and 51/134 participants (38.1%) were diagnosed with other diseases. Via histopathology, 70/134 participants (52.3%) were diagnosed with dysplasia, and 58/134 (43.3%) were diagnosed with benign conditions. The specialist's diagnoses exhibited a higher specificity, positive predictive value, and accuracy than the primary examiners. A specialist using the current TNOMSP for high-risk participants diagnosed OPMDs with dysplasia more accurately than a primary examiner. Early diagnosis of high-risk OPMDs is crucial in countries with a high prevalence of the disorders. Proficient examination via the current TNOMSP by trained clinician is effective for the management of OPMDs with dysplasia.